Oxaloacetate acid ameliorates paraquat-induced acute lung injury by alleviating oxidative stress and mitochondrial dysfunction - Li, Wenwen; Li, Mengxuan; Chen, Kaiyuan; Tang, Yahui; Yin, Ran; Lan, Linhua; Hong, Guangliang (Frontiers in Pharmacology, 2022)
Acute lung injury (ALI) is the primary cause of death among patients with acute paraquat (PQ) poisoning, whereby peroxidative damage is an important mechanism underlying PQ-induced lung injury. There is a lack of effective interventional drugs for patients with PQ poisoning. Oxaloacetic acid (OAA) participates in multiple in vivo metabolic processes, whereby it facilitates the clearance of reactive oxygen species (ROS) and improves mitochondrial function. The study aimed to assess the protective effects of OAA on PQ-induced ALI and elucidate the underlying molecular mechanism. Our data demonstrated that OAA treatment significantly alleviated PQ-induced ALI and improved the survival rate of PQ-poisoned mice, and also alleviated PQ-induced cellular oxidative stress and mitochondrial dysfunction. OAA-mediated alleviation of PQ-induced mitochondrial dysfunction depends on the following mechanisms which may explain the above findings: (1) OAA effectively cleared intracellular ROS, inhibited ROS accumulation, and mitochondrial depolarization; (2) OAA inhibited the downregulation of L-OPA1 and MFN2 caused by PQ and promoted a dynamic balance of mitochondrial fusion and fission, and (3) the expression of PGC-1α, TFAM, COX2, and COX4I1, increased significantly following OAA intervention which improved mitochondrial respiratory functions and promoted its biogenesis and energy metabolism in damaged cells. In conclusion, OAA effectively cleared ROS and improved mitochondrial dysfunction, thereby significantly improving ALI caused by PQ poisoning and the animal survival rate. Therefore, OAA may be a potential drug for the treatment of PQ poisoning.